2012
DOI: 10.1590/s1415-790x2012000400019
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review versus internet search: considerations about availability and reliability of medical information regarding pregnancy in women with multiple sclerosis

Abstract: Evidence-based studies conducted under the strictest rules for careful systematic reviews and meta-analyses should be available with open access, i.e. accessible without payment of a fee, thereby enabling worldwide knowledge on matters of great interest to healthcare providers and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In our study, the frequency of spontaneous abortion was found to be similar to that observed in the general Turkish population (20.9% in MS, 20.5% in general Turkish population) [17]. In the former study, the abortion rate was reported to be 27.9% including both miscarriages and medical abortions [31]. In our data sheet, we recorded spontaneous and medical abortions separately.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our study, the frequency of spontaneous abortion was found to be similar to that observed in the general Turkish population (20.9% in MS, 20.5% in general Turkish population) [17]. In the former study, the abortion rate was reported to be 27.9% including both miscarriages and medical abortions [31]. In our data sheet, we recorded spontaneous and medical abortions separately.…”
Section: Discussionsupporting
confidence: 79%
“…Most of the studies have not shown any negative effect of a pregnancy on long-term disease course/progression or disability [32]; some even reported favorable effects [12,29,31]. We showed that MS patients who had only 1 pregnancy had a higher conversion rate from RRMS to SPMS than MS patients with 2 or more pregnancies (p = 0.001).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation